To Veil or not to Veil: Tracing the Hijab in Contemporary Muslimah’s Writings - Shaikh, Neda Parvin (UIN Syarif Hidayatullah Jakarta, 2023)
This research examines the constructions of Muslimah or Muslim women's identity through the lens of religious clothing, specifically the hijab, as depicted in two contemporary Muslimah literary texts. Randa Abdal Fattah’s Does My Head Look Big In This? (2005) is a bildungsroman told from the perspective of a sixteen-year-old Australian-Palestinian Muslim girl who makes the life-changing decision to wear the hijab. The second novel is Leila Aboulela’s Minaret (2005), tracing the journey of a young female Sudanese immigrant in London who finds herself struggling socially, economically and culturally in a foreign country after leaving behind a life of affluence in Sudan. Using theories such as Homi K Bhabha’s Cultural Hybridity and Miriam Cooke’s Islamic Feminism, the article analyses the protagonists’ choice of veiling and the internal and external factors that influence this difficult decision. The analysis suggests that female hybrid identities in Western diasporic contexts are uniquely configured through religious and cultural markers like the hijab that forge feminist bonds and reignite connections to the Homeland and God. The decision to wear the hijab also helps counter Western stereotypes related to Islam and Muslim women. The hijab has also become a contentious issue in recent times. It is thus imperative to look closely at contemporary Muslimah literature that addresses this topic, especially those written by Muslimah authors. This research helps to reduce mainstream misrepresentation and contest stereotypes, thereby making space for newer ways of reading Muslim identities and feminist tendencies.